ANALISIS KINERJA PT MATAHARI DEPARTMENT STORETBK PASKA DIMULAINYA PANDEMI COVID-19 - Sunaryono, Sunaryono (Jurnal Ekonomi STIEP ( JES ), 2021)
This research aims to determine the financial performance of PT Matahari Department Store Tbk before and after the Covid-19 pandemic was started so that it can be observed the increase or decrease after the Covid-19 pandemic was started. The data used are the financial statements of the posted-Pandemi Covid-19 of PT Matahari Department Store Tbk before the covid-19pandemicwas started in the January-December 2019 and after the covid-19 pandemic was started in the January - December 2020 period. Data analysis using Du Pont System Analysis. The results showed an increase in the financial ratios before the covid-19 pandemic started and after the covid-19 pandemic started. This is indicated by the achievement of an increase in the percentage of Return on Investment, Return on Assets, Cash Ratio, Current Ratio, Collection Period, Inventory Turn Over, Total Asset Turn Over, and Total Equity so that the increase can prove that the research hypothesis proposed that after a covid-19 pandemic is proven to experience efficiency and decrease its financial performance.